The influence of lifestyle of obstetrics and gynecology female residents on gynecological and obstetrical outcomes in Saudi Arabia - Al Qahtani, Nourah Hassan; Alomireeni, Aseel Ali; Ali Shaker Hasan Abdulla, Eman; Ali Shaker Hasan Abdulla, Zainab; Alshammari, Nebras Abdulwahab; Leheidan, Shahad Mohamed; Aljehani, Danah Meshal; Abdullah Al Hamdan, Kholoud; Alwabari, Salsabeel Salman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Obstetrics and gynecology (OB/residency is characterized by long working hours, high clinical demands, and significant psychological stress. These factors may adversely affect the lifestyle and reproductive health of female residents. The aim of the study was to investigates the impact of OB/GYN residency on physical well-being, mental health, and gynecological and obstetric outcomes compared to women from the general population. Methods: A cross-sectional study was conducted between January and August 2024 using a culturally adapted, pilot-tested online questionnaire distributed to Saudi married women with children. Participants included 119 OB/GYN female residents and 91 age-matched controls. Data collected included demographic information, lifestyle characteristics, work-related stress indicators, menstrual and reproductive history, and obstetric outcomes. Statistical analyses were performed using SPSS version 25, with Chi-square and Mann-Whitney U tests applied for group comparisons (p<0.05). Results: OB/GYN residents reported significantly higher rates of sleep disturbances (72.3% vs. 29.7%), concentration difficulties (71.4% verses 45.1%), and perceived work-related stress (>8/10: 44.5% verses 5.5%) compared to controls (p<0.001). They also reported significantly less sleep (<6 hours: 60% verses 30.8%). Despite similar BMI, dietary habits, and exercise routines between groups, pregnancy complications were more frequent among residents (51.3% verss 35.2%, p=0.02), and they had significantly lower pregnancy rates (p=0.0001). No significant differences were found in abortion rates, cesarean deliveries, or labor augmentation. Conclusions: OB/GYN residency is associated with increased psychological and lifestyle stressors that may negatively impact reproductive health. Although residents reported comparable happiness levels, their higher stress, reduced sleep, and lower pregnancy rates with increased complications underscore the need for supportive policies to enhance well-being. Future research should focus on targeted interventions to mitigate stress and improve health outcomes among female medical residents.